African Union's quest for peace in Somalia: Contextualizing the transition from AMISOM to ATMIS 1 - Ajú, M. M. (The Horn of Africa since 2018: Continuities, transformations, and prospects, 2025)
Authorized in March 2007, AMISOM’s mandate officially ended on March 31, 2022 giving place to a newly established African Union Transition Mission in Somalia that came into effect on April 1, 2022. After 15 years of mixed results of success and failure between 2007 and 2022, the African Union has remained resolute in its commitment and on course with the quest for peace and consolidation of state-building in Somalia. It now has a heightened sense of determination with ambitious and clearly defined targets for its mission, tight deadlines, and a well-defined exit strategy, something that was missing before. This chapter explores the challenges of a transition and highlights the salient and possibly insurmountable onus placed into the hands of a still weak Federal Government of Somalia. More specifically, it discusses the prospect for peace and security in the most conflict-ridden nation of the Horn of Africa with the related regional implications and beyond in a post-AMISOM landscape. An assessment of AMISOM’s experience and the overly ambitious transition plan suggests that the emerging scenario could yet again fall short of expectations in the quest for stability and lasting peace will continue to remain an elusive grand ambition.